Mortality And Body Weight Loss Of Broiler Chicken During Different Time Transportation From Gunungsitoli City To Nias Selatan Regency - Zebua, Cipta Kasih Novilita; Karolina Deko, Maria; Menoh, Yori R; Mendrofa, Seftinus (Jurnal Peternakan Nusantara, 2025)
Transportation of broiler chickens is very crucial because it determines the level of welfare of the livestock, especially economic losses due to decreased performance. Transportation of broiler chickens greatly influences mortality and body weight loss. One thing that can be done to minimize mortality and weight loss is management of livestock transportation time. The aim of this research was to determine the effect of transportation time for broiler chickens on mortality and body weight loss. Data were analyzed using descriptive analysis to determine the effect of differences in transportation time on the performance of broiler chickens. The results of the research showed that the transportation of broiler chickens carried out in the morning experienced a loss of 0.5 kg, while the transportation of broiler chickens carried out in the afternoon experienced a weight loss of 4,0 kg. Furthermore, in transportation in the morning there were no deaths at all, while in transportation in the afternoon the mortality was 0.29%.